Characterization of the complete chloroplast genome of sugar maple (Acer saccharum) - Deng, Xin (Mitochondrial DNA B Resour, 2019)
Acer saccharum is one ecologically and economically important tree species cultivated widely across the world. In this study we generated the complete chloroplast (cp) genome of A. saccharum via genome-skimming method. The assembled genome is 155,684 base-pairs (bp) in size, with one large single copy region of 85,393 bp and one small single copy region of 18,033 bp separated by two inverted repeats of 26,129 bp. The genome contains a total of 133 genes, including 85 protein-coding genes, 8 rRNAs and 40 tRNAs. Furthermore, phylogenomic estimation strongly supported A. saccharum as a distinct lineage within the monophyletic Acer.